Semipolar GaN templates on sapphire: 432 nm InGaN light-emitting diodes and light extraction simulations. (7th February 2018) - Khoury, Michel; Li, Hongjian; Bonef, Bastien; Kuritzky, Leah Y.; Mughal, Asad J.; Nakamura, Shuji; Speck, James S.; DenBaars, Steven P.
Abstract: Semipolar InGaN 432 nm light-emitting diodes were demonstrated on semipolar GaN templates grown on patterned sapphire. Packaged devices exhibited a light output power of 4.7 mW at 100 A/cm 2 and a peak external quantum efficiency of 1.3%. Atom probe tomography characterization indicated detectable bending in quantum wells as a result of significant roughening from regrowth on the semipolar templates, while no indium clustering effect was observed. Light extraction simulations were also performed to estimate the improvement in light extraction efficiency using patterned sapphire compared with the use of planar templates.